ANALISIS KEBUTUHAN GURU DALAM PENGIMPLEMENTASIAN KURIKULUM 2013 DI SEKOLAH DASAR - Nurcholis Sunuyeko; Ahmad Lani; Lilik Wahyuni (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2016)
Abstract: The study aims at mapping Malang’s primary school teachers need in implementing 2013 Curriculum. The study was a survey and need assessment study. The data were obtained through observation, questionnaire, in-depth interview, and focusing group discussion (FDG). The data, later, were analysed in the qualitative and quantitative analysis. The result of the study showed that Malang’s primary school teachers’ needs are: 1) standard materials to socialize 2013 Curriculum, 2) guidelines in the form of document, 3) in-depth training, 4) detailed explanation of 2013 Curriculum, 5) socialization or training for all primary school teachers, 6) re-explanation for teacher better understanding, and 7) special training on evaluation. Abstrak: Penelitian ini bertujuan mendapatkan peta kebutuhan guru SD Kota Malang dalam pengimplementasian Kurikulum 2013. Penelitian menggunakan rancangan survey dan need assesment. Teknik pengumpulan data observasi, angket, wawancara mendalam, dan focusing group discussion (FDG). Analisis data secara kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa kebutuhan guru SD kota Malang adalah (1) bahan sosialisasi kurikulum 2013 yang baku, (2) panduan dalam bentuk dokumen, (3) pelatihan yang mendalam, (4) penjelasan yang lebih rinci tentang kurikulum 2013, (5) pembinaan atau sosialisasi kepada semua guru, (6) penjelasan ulang agar guru bisa memahami dengan lebih baik, dan (7) pelatihan khusus tentang cara mengevaluasi.